2006
DOI: 10.1103/physrevlett.97.055502
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Ripples on Phononic Crystals Reveals Acoustic Band Structure and Bloch Harmonics

Abstract: Broadband surface phonon wave packets on a phononic crystal made up of a microstructured line pattern are tracked in two dimensions and in real time with an ultrafast optical technique. The eigenmode distribution and the 2D acoustic band structure are obtained from spatiotemporal Fourier transforms of the data up to 1 GHz. We find stop bands at the zone boundaries for both leaky-longitudinal and Rayleigh waves, and show how the structure of individual acoustic eigenmodes in k space depends on Bloch harmonics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…(For a more detailed description, see the Supplementary Information.) Recently, this method has been applied to the investigation of phononic crystals 20 . By recovering the wavevectors as a function of time, we can investigate the dynamics of the individual eigenstates.…”
mentioning
confidence: 99%
“…(For a more detailed description, see the Supplementary Information.) Recently, this method has been applied to the investigation of phononic crystals 20 . By recovering the wavevectors as a function of time, we can investigate the dynamics of the individual eigenstates.…”
mentioning
confidence: 99%
“…Instead of a single-point measurement, the sample may also be scanned to obtain two-dimensional images of wave propagation [60,61]. The technique has recently also been applied to study wave interaction with phononic crystal samples [62][63][64][65].…”
Section: Optical Characterization Of Surface Vibrationsmentioning
confidence: 99%
“…This line scan method has been used together with angular spectrum theory to characterize both the slowness and wave attenuation [15]. On the other hand, time-domain optical pump-probe characterization has been used for spot excitation of waves and observation of the resulting ripples on the crystal surface [63]. It has been demonstrated that a few acoustic wave lengths away from the source, the phase front follows the shape of the surface wave, i.e., the locus of the group velocity as a function of the propagation angle.…”
Section: Wave Slowness From Random Saw Fieldsmentioning
confidence: 99%
“…It has been used to investigate the dispersion relation of surface acoustic modes [42], acoustic band structure [43] and to observe the diffraction angles [44]. In infinite space and time domains, the FT is written as…”
Section: A Diffraction Effect -Spatial Filteringmentioning
confidence: 99%